Potential corruption due to the change from the death penalty to life imprisonment in Indonesia's New Criminal Code - Erdianto Effendi; Elya Kusuma Dewi; Geofani Milthree Saragih (Komisi Pemberantasan Korupsi, 2025)
Capital punishment has long been used as a form of punishment for serious crimes, including corruption, with the aim of deterring and preventing offenses that harm the state and society. This study examines the impact of replacing the death penalty with life imprisonment in Indonesia’s new Criminal Code, particularly on efforts to eradicate corruption and its implications for law enforcement. The study employs a normative legal method, using legislative, conceptual, and comparative approaches to explore the historical application of the death penalty for corruption offenses, compare practices in countries such as China and Saudi Arabia that still enforce capital punishment, and analyze the policy shift in the Indonesian context. The findings indicate that replacing the death penalty may weaken its deterrent effect and increase the risk of corruption, especially if not supported by policies that strengthen law enforcement. Nevertheless, this change aligns with the principle of human rights protection, which is a key consideration in modern legal systems. This study recommends alternative measures such as asset forfeiture, the imposition of maximum fines, restrictions on political rights, and enhanced transparency and oversight to promote more effective and equitable anti-corruption policies.